Deletion analysis of the maize mitochondrial superoxide dismutase transit peptide. - White, J A (1989)
The maize mitochondrial superoxide dismutase (SOD; EC 1.15.1.1), a nuclear gene product, has been previously shown to be imported into maize mitochondria. The cDNA for maize mitochondrial SOD was subcloned into a vector containing the T7 promoter. Deletions were made in the transit peptide coding region of the cDNA. The undeleted and deleted proteins were synthetically produced by transcription and translation in vitro. Undeleted preSOD-3 is translocated into isolated maize mitochondria with an efficiency of approximately 30%. Mature SOD-3 subunits are recovered from the matrix but not the membranes of subfractionated mitochondria. These subunits are assembled into the tetrameric holoenzyme. The modified SOD-3 precursors are imported into mitochondria at lower efficiencies than undeleted preSOD-3. The relative import efficiency appears to be dependent upon the deletion size. To our knowledge such analysis of a plant mitochondrial precursor protein has not been reported previously.